Штампы V-VII вв. на посуде группы «Африканской краснолаковой» из раскопок Херсонесского городища - Голофаст, Л.А. (Материалы по археологии, истории и этнографии Таврии, 1996)
Одним из наиболее массовых материалов, встречаемых при раскопках Хер- сонесского городища в слоях V-VII вв., является краснолаковая керамика, в том числе со штампованными украшениями. Из последних опубликовано лишь несколько Предлагаемая статья является публикацией штампов на посуде группы “Африканской краснолаковой” из коллекции Херсонесского заповедника и Государственного Эрмитажа The collection of stamps on African Red Slip wares from Chersones site numbers 19 specimens. Some of them occurred in archaeological context: 1 - from the layer of the second quarter of the 5th c. residual; 4 - from the context of the late 6th c. - mid. 5th c.; 7 - from the layer of the second half/mid. of the 6th c. residual: 8 - from the third quarter 6th c. filling of a cistern - residual; 10 - from the layer of the late 4th - mid. 5th c.c.; 13 - from the second / third quarter of the 6th c. deposit; 14 - with material of the mid. 6th - mid. 7th c.c.; 17 and 18 occurred in the first half of the 7th c. deposit all the rest were found out of context. The published collection, though not very large, adds some new motifs to the repertoire of stamps on the African Red Slip wares.